Beyond totalitarianism : Stalinism and Nazism compared - Geyer, Michael, 1947-; Fitzpatrick, Sheila (New York, N.Y. : Cambridge University Press, 2009)
"In essays written jointly by specialists on Soviet and German history, the contributors to this book rethink and rework the nature of Stalinism and Nazism and establish a new methodology for viewing their histories that goes well beyond the now-outdated twentieth-century models of totalitarianism, ideology, and personality. Doing the labor of comparison gives us the means to ascertain the historicity of the two extraordinary regimes and the wreckage they have left."--Jacket
Introduction: after totalitarianism : Stalinism and Nazism compared / Michael Geyer with assistance from Sheila Fitzpatrick -- Governance -- The political (dis)orders of Stalinism and National Socialism / Yoram Gorlizki and Hans Mommsen -- Utopian biopolitics: reproductive policies, gender roles, and sexuality in Nazi Germany and the Soviet Union / David L. Hoffmann and Annette F. Timm -- Violence -- State violence : violent societies / Christian Gerlach and Nicolas Werth -- The quest for order and the pursuit of terror: National Socialist Germany and the Stalinist Soviet Union as multi-ethnic empires / Jörg Baberowski and Anselm Doering-Manteuffel -- Socialization -- Frameworks for social engineering: Stalinist schema of identification and the Nazi Volksgemeinschaft / Christopher R. Browning and Lewis H. Siegelbaum -- Energizing the everyday: on the breaking and making of social bonds in Nazism and Stalinism / Sheila Fitzpatrick and Alf Lüdtke -- The new man in Stalinist Russia and Nazi Germany / Peter Fritzsche and Jochen Hellbeck -- Entanglements -- States of exception: the Nazi-Soviet war as a system of violence, 1939--1945 / Mark Edele and Michael Geyer -- Mutual perceptions and projections: Stalin's Russia in Nazi Germany: Nazi Germany in Stalin's Russia : Nazi Germany in the Soviet Union / Katerina Clark and Karl Schlögel.
Includes bibliographical references (pages 443-516) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Totalitarianism; Soviet Union -- Politics and government; Germany -- Politics and government -- 1933-1945.; Totalitarisme; URSS -- Politique et gouvernement; Allemagne -- Politique et gouvernement -- 1933-1945.; totalitarianism; POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism; Politics and government; Totalitarianism; Germany; Soviet Union; Stalinisme; Nationaal-socialisme.; Sovjet-Unie.; Duitsland; 1933-1945; dissertations; Academic theses; Academic theses; Thèses et écrits académiques.